Determination of the critical current density in superconducting films : comparison of a measured magnetic flux distribution with model calculations - Kirchgässner, David; Brüll, Peter; Leiderer, Paul (My University, 1992)
We have investigated the magnetic field distribution of an epitaxial Y Ba2 Cu3 O7-x film and compared the result with a theoretical calculation which has recently been proposed. This model takes into account the strong demagnetization effects that occur if a thin superconducting film is exposed to an external magnetic field perpenicular to the sample plane. It describes the magnetic field distribution of a two opposing current bands, both carrying the critical current density jc. We use jc as a fit parameter and find very good agreement between the measured and the calculated field distributions.
Keywords: critical current density; 530